Assessing knowledge acquisition and perceptions in hands-on video editing workshop for non-technical students - Bohari, Zubaidah; Abdul Talip, Abdul Hadi; Julaihi, Satria Arjuna; Che Md Nor, Rumaizah; Ibrahim, Norizuandi (UiTM Cawangan Perlis, 2025)
In the era of digital technology, video editing is now a priority skill in various fields like education, marketing, and business. Nevertheless, non-technical students tend to lack video editing skills because of their limited exposure to montage elements and video editing software. This research explores the effects of practical video editing workshops on knowledge and perceptions of non-technical students. The workshops were aimed at imparting knowledge of montage elements, a key component of video production. With a quantitative research design, 30 students from non-technical disciplines have participated in guided workshops with Microsoft PowerPoint and CapCut. The findings indicate a significant improvement in the comprehension of montage elements, including visual organization, audio synchronization, transitions, and pacing among the students, with high mean knowledge scores (3.97 - 4.05) on a 5-point scale. In addition, regression analysis shows a significant relationship (p-value < 0.05), confirming its effectiveness in engaging non-technical students and achieving a better understanding of video editing concepts. The results of this research contribute to the development of instructional strategies that promote improved learning experiences for groups of students with varying backgrounds.